Overcoming challenges on using native seeds for restoration of megadiverse resource‐poor environments: a reply to Madsen et al. Issue 6 (25th September 2016) - Dayrell, Roberta L. C.; Arruda, André J.; Buisson, Elise; Silveira, Fernando A. O.
Abstract: Madsen et al. (2016) reviewed several major limiting factors to establishment of seedlings in nonforest ecosystems (NFE), and proposed seed enhancement technologies to overcome these restoration barriers. However, biodiverse nutrient‐poor NFE present additional hurdles that preclude landscape‐scale seed‐based restoration and were not mentioned in their review. Here, we discuss issues related to native seed availability and provenance, and shortfalls in knowledge on seed quality testing and dormancy release that severely hamper restoration of degraded nutrient‐impoverished NFE. We present alternatives for overcoming these challenges and highlight the need for investments to find more practical and cost‐effective options for broad‐scale restoration.